Data (images) for: New barcodes of freshwater diatoms from Sweden - Kahlert, Maria; Mora, Demetrio; Kusber, Wolf-Henning; Abarca, Nélida; Zimmermann, Jonas (Swedish University of Agricultural Sciences, 2026)
The published data are images of freshwater diatoms, taken within the national barcoding project FRESHBAR (2019-2023), a research project focusing on the development of DNA methods for national environmental monitoring. The project was financed by the Environmental Protection Agency’s environmental research grant in collaboration with the Swedish Agency for Marine and Water Management. The aim of the project was to establish as many diatom cultures as possible, to generate their barcodes, to identify them to the lowest taxonomical level possible, and to make all results, data and material publicly available for further research and usage within environmental monitoring. FRESHBAR represents the first large-scale effort to generate barcode reference sequences for Nordic freshwater benthic diatoms. The images are part of the results. Images of living and prepared strains are stored with open access (license: CC0) in the e-archive of the Swedish University of Agricultural Sciences (SLU), available under the permanent link https://hdl.handle.net/20.500.12703/6968. Images are stored in different subfolders, grouped by taxon. Information on storage is found when searching in the menu “By subject”, where the metadata are found under “FRESHBAR images” in the file “FRESHBAR picture images SLU archive.xlsx”. Images taken with LM are stored in the subfolder https://hdl.handle.net/20.500.12703/6822, SEM images in the subfolder https://hdl.handle.net/20.500.12703/6823. Metadata are stored in the subfolder https://hdl.handle.net/20.500.12703/6825. In order to find a specific image item, you can locate the handle in the provided mapfiles.txt, and then go to https://hdl.handle.net/[handle], e.g. for https://hdl.handle.net/20.500.12703/6885 for SEM 1C11.

De publicerade data är bilder av sötvattenskiselalger tagna inom forskningsprojektet FRESHBAR. FRESHBAR var ett av åtta forskningsprojekt med fokus på utveckling av DNA-metoder för nationell miljöövervakning. Projektet har finansierats med medel från Naturvårdsverkets miljöforskningsanslag som finansierar forskning till stöd för Naturvårdsverkets och Havs- och vattenmyndighetens kunskapsbehov. Se vidare under den engelska beskrivningen för mera info.
Data (bilder) för: Nya streckkoder för Svenska kiselalger från sötvatten
FRESHBAR diatom images
Keywords: bacillariophyceae species richness; freshwater; sötvatten; diatoms; microscopes; mikroskop; DNA barcodes; dna-streckkoder; photographs; fotografier; reference libraries; referensbibliotek; bacillariophyta; Botany; Botanik; Genetics and Genomics; Genetik och genomik; Other Biological Topics; Annan biologi; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap